Do Corporate Cash Holdings Matter for ESG Performance? Empirical Evidence from India - Joshi, Bhavya; Joshi, Himanshu (Prabandhan: Indian Journal of Management, 2024)
Purpose : The study investigated the relationship between a firm’s cash holdings and its ESG performance, recognizing environmental, social, and governance (ESG) as a driver of long-term value creation. Methodology : The study examined a sample of 98 Indian firms listed on the National Stock Exchange over six years (2017–2022). We employed panel data analysis using pooled ordinary least squares, random effects, and fixed effects models. The Lagrange multiplier and Hausman tests were used to determine the appropriate panel data model, which validated our approach. Findings : Our results showed a positive association between cash holdings and overall ESG scores as well as ESG pillar scores. Robust cash flow also enabled firms to allocate resources to ESG activities, with cash holdings having a similar positive impact on all three ESG dimensions. Practical Implications : Even if there were no obvious immediate financial gains, companies with larger cash holdings could invest in ESG projects and improve long-term ESG performance. Originality : The study extended earlier research on ESG practices by offering new evidence that cash holdings improved ESG performance.